The Eritrean Diaspora in Milan Successful and Unsuccessful Models of Aging - Gardini, Marco (Ledizioni, 2022)
This report is the result of fieldwork research conducted under the framework of TAAD ("The Aging African Diasporas: Perspectives from Lombardia"), a project led by Prof. Alice Bellagamba (University of Milano-Bicocca) that for three years has investigated the meanings of aging for members of the Eritrean, Senegalese, and Egyptian diasporas in Lombardy. More specifically, this report explores the results that emerged from semi-structured interviews and informal conversations with 68 people of Eritrean origin (36 women and 32 men) collected in Milan and its province between 2018 and 2020. The great majority of my interlocutors were over 65 years old and moved to Italy between the end of the 1960s and the 1980s, but younger members of the diaspora have been also interviewed to better address how meanings of aging change along generational lines. Since the beginning of the lockdown imposed by the Covid-19 pandemic in March 20201, some of these conversations have been conducted using telephonic or online means of communication. In this report I use pseudonyms and other precautions to guarantee the complete anonymity of my interlocutors.